1973
DOI: 10.1172/jci107214
|View full text |Cite
|
Sign up to set email alerts
|

The Stimulation of 1,25-Dihydroxycholecalciferol Metabolism in Vitamin D-deficient Rats by 1,25-Dihydroxycholecalciferol Treatment

Abstract: A B S T R A C r Daily oral administration of 1,25-dihvdroxycholecalciferol to vitamin D-deficient rats increases the rate of disappearance of [3H]1,25-dihydroxycholecalciferol and increases the rate of appearance of metabolites both less polar and more polar than 1,25-dihydroxycholecalciferol in the intestine, bone, liver, kidney, plasma, and muscle. Since 1,25-dihydroxycholecalciferol is believed to be the metabolically active form of vitamin D in the stimulation of intestinal calcium transport and bone calci… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
11
0

Year Published

1973
1973
2014
2014

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 60 publications
(12 citation statements)
references
References 26 publications
1
11
0
Order By: Relevance
“…In the case of glucose, using a tracer dose of [ 14 C] glucose, Zilversmit (1960) observed that the fractional turnover rate for blood glucose in humans was 0路1/h and the pool size 5 g. When 50 g glucose was administered intravenously the turnover rate was 1路0/h, a 10-fold increase (Karam et al 1986) and when the absolute turnover rate was calculated the difference in the rate of glucose disposal between the physiologic and pharmacologic doses was 100-fold. Similar effects have been noted with the turnover of 1,25-dihydroxycholecalciferol before and after loading with the hormone (Frolik & DeLuca, 1973).…”
Section: Discussionsupporting
confidence: 80%
“…In the case of glucose, using a tracer dose of [ 14 C] glucose, Zilversmit (1960) observed that the fractional turnover rate for blood glucose in humans was 0路1/h and the pool size 5 g. When 50 g glucose was administered intravenously the turnover rate was 1路0/h, a 10-fold increase (Karam et al 1986) and when the absolute turnover rate was calculated the difference in the rate of glucose disposal between the physiologic and pharmacologic doses was 100-fold. Similar effects have been noted with the turnover of 1,25-dihydroxycholecalciferol before and after loading with the hormone (Frolik & DeLuca, 1973).…”
Section: Discussionsupporting
confidence: 80%
“…Comparing the responses to low dietary calcium at the age of [20][21][22][23][24] ing WKY, P < 0.005 (Fig. 3).…”
Section: Resultsmentioning
confidence: 99%
“…The stimulation of intestinal calcium and phosphorus transport both appear to be mediated by the 1,25-dihydroxy metabolite of vitamin D synthesized by the kidneys (11,12) from 25-hydroxycholecalciferol (25-OHD3)' which is derived from the hepatic hydroxylation of vitamin D3 (13). The earlier reported failure of orally administered 1,25-dihydroxycholecalciferol (1,25-(OH)2Da) to cure the rachitic state in rats (14) has now been attributed to the more rapid clearance of 1,25-(OH)2Ds relative to its immediate precursor, 25-OHD8 (15), which was effective in this regard. Accordingly, the 1,25-dihydroxy metabolite of cholecalciferol is considered to be the physiologically active form of the vitamin in mediating the mobilization of calcium and phosphorus from the intestine and bone.…”
Section: Introductionmentioning
confidence: 99%